Analysis Of Hotel Façade And Cooling Energy Consumption In Penang - Abdul Nasir, Muhammad Hafeez (2021)
The research investigates the thermal performance of building facade of high-rise hotels in the hot and humid climate of George Town, Penang. The research identifies the problem of inefficient facade design as main contributors to air conditioning high cooling energy consumption for hotels. In response, six case studies of high-rise hotels were systematically selected to measure the façade thermal performance on the west orientation. Three performance measurable scales proposed including the infrared thermography of average external surface temperature, the manual calculation of Overall Thermal Transfer Value (OTTV) and the guestroom space cooling load simulation alongside energy use cost estimation. Initial hypotheses predict the increase in average surface temperature corresponds to increase in OTTV and the average cooling load. The findings revealed the average surface temperature of the selected hotel facades ranging between 33.3 ℃ and 35.9 ℃ from January to June. While, the OTTV on the west facade ranges from 38.6 Wm-2 to 122.9 Wm-2 with a majority of the hotels have failed to meet the weighted average heat gain as recommended by Malaysian Standards MS1515 of less than 50 Wm-2. While, the average guestroom cooling load of selected cases range between 77.9 Wm-2 and 131.2 Wm-2 equivalent to annual cooling energy consumption costs between RM 249/m2 and RM 357/m2. Additionally, the results of the research revealed the average surface temperature establishes an insignificant correlation with the average cooling load while a strong linear correlation is observed between OTTV and the average cooling load